2020
DOI: 10.1016/j.seizure.2019.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic outcome and access to care in adults with epilepsy in Sweden: A nationwide cohort study

Abstract: Epilepsy has well-documented associations with low income and low education levels, but the impact of a patient's socioeconomic standing (SES) on the effects of epilepsy have been less studied. Method: We performed a register-based cross-sectional study and asked if SES was associated with more severe epilepsy or limited access to care in Sweden, where health care is universal, and if socioeconomic outcomes (employment and income) differed for persons with epilepsy (PWE) with different levels of educational at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 20 publications
(32 reference statements)
0
17
0
Order By: Relevance
“…4 One study of all adult patients with epilepsy in the Swedish patient register in 2000 to 2015 (n = 126,406) and controls (n = 379,131) matched for age, gender, and place of birth, showed that while low educational attainment was associated with low levels of income and inversely associated with employment in both PWE and controls, these associations were much more noticeable in PWE than controls. 12 One study showed that higher education level, higher self-determination, lower family overprotection, and generalized epilepsy were significant predictors for higher employability in PWE. 13 PWE may benefit from vocational rehabilitation services; of the 2,030 previously unemployed PWE in one study, who received vocational rehabilitation services, 884 (43.5%) achieved successful competitive employment.…”
Section: Discussionmentioning
confidence: 99%
“…4 One study of all adult patients with epilepsy in the Swedish patient register in 2000 to 2015 (n = 126,406) and controls (n = 379,131) matched for age, gender, and place of birth, showed that while low educational attainment was associated with low levels of income and inversely associated with employment in both PWE and controls, these associations were much more noticeable in PWE than controls. 12 One study showed that higher education level, higher self-determination, lower family overprotection, and generalized epilepsy were significant predictors for higher employability in PWE. 13 PWE may benefit from vocational rehabilitation services; of the 2,030 previously unemployed PWE in one study, who received vocational rehabilitation services, 884 (43.5%) achieved successful competitive employment.…”
Section: Discussionmentioning
confidence: 99%
“…Persons with epilepsy and low socioeconomic status (SES) seem to have more severe epilepsy, higher rates of emergency visits, hospitalizations, and breakthrough seizures 1,2 compared to persons with high SES. Regarding access to care, low SES has been associated with longer time to epilepsy surgery 3 and lower access to a neurologist 1,4,5 which may influence the prescription of anti‐seizure medication (ASM). In Sweden, it was found that neurologists more commonly prescribed lamotrigine and levetiracetam compared to non‐neurologists and persons with epilepsy and high SES were more commonly prescribed lamotrigine and less commonly prescribed valproate (VPA, valproic acid) than persons with lower SES 5 .…”
Section: Introductionmentioning
confidence: 99%
“…epilepsy surgery 3 and lower access to a neurologist 1,4,5 which may influence the prescription of anti-seizure medication (ASM). In Sweden, it was found that neurologists more commonly prescribed lamotrigine and levetiracetam compared to non-neurologists and persons with epilepsy and high SES were more commonly prescribed lamotrigine and less commonly prescribed valproate (VPA, valproic acid) than persons with lower SES.…”
mentioning
confidence: 99%
“…In this context, perceived financial distress might have been important for mortality as it has been linked to ASM non-compliance in other research 38 . It is also possible that educational differences with respect to access to specialist epilepsy care that have been observed in other settings 27 , 39 might have been exacerbated in this period although we observed a sharp fall in epilepsy ASMRs among the low educated in Latvia, where there is some evidence that unmet medical need grew sharply in 2010–2012 due to an inability to afford medical care 40 .…”
Section: Discussionmentioning
confidence: 58%
“…It is possible that various factors might play a role in the increased prevalence of epilepsy mortality among low educated individuals. For example, lower education has been associated with more severe epilepsy as measured by hospitalisation/the frequency of hospitalisations 27 , 28 , while other research has linked lower area socioeconomic status (SES) to emergency medical service assignments for seizures 29 and individual socioeconomic disadvantage to poor seizure control 30 . This might be important as seizure frequency and severity have been linked to an increased risk for mortality 31 , specifically, SUDEP 32 .…”
Section: Discussionmentioning
confidence: 99%